Eulohiya Para Sa Mga Kaibigang Tinahak Ang Landas Na Hindi Gaanong Nilalakbay - Yambao, Yayo Winter Sun (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
The essay honors the volunteer teachers and workers who tirelessly and selflessly served the marginalized Lumad indigenous peoples in the time of the COVID-19 pandemic and militarized lockdown. It also informs us of what the pandemic means and does to the internally displaced Lumad, who are unfaltering in their struggle to fight for their right to education, land, and essential social services.